The relationship between lifestyle factors and outcome of treatment with TNFα inhibitors in axial spondyloarthritis – results from 14 European countries - Gareth T. Jones; Ovidiu Rotariu; Ross MacDonald; Brigitte Michelsen; Bente Glintborg; Irene van der Horst-Bruinsma; Bjorn Gudbjornsson; Arni Jon Geirsson; Heikki Relas; Pia Isomäki; Jakub Závada; Karel Pavelka; et al. (BMC Rheumatology)
Abstract Objectives To quantify the influence of lifestyle factors on tumour necrosis factor inhibitor (TNFi) treatment response, in axial spondyloarthritis (axSpA). Methods Data on biologics-naïve adults with axSpA were captured from European rheumatology registries. Information on lifestyle factors (smoking, overweight/obesity, and/or alcohol consumption) were identified ± 30 days of commencing their first TNFi. Treatment response (BASDAI-50, ASDAS or ASAS response criteria) was determined at 3 and 12 months. In separate models, the relationship between treatment response and baseline smoking, BMI and alcohol was assessed using logistic regression, adjusted for age, sex, country, calendar year of treatment initiation, disease duration and baseline disease activity. Results From 14 registries, 14,885 patients were included. Of those with available data, 29% were current smokers, 49% current drinkers, 37% were overweight and 21% were obese. At 12 months, smokers were less likely to achieve BASDAI-50 treatment response compared to non-smokers (adjusted odds ratio: 0.77; 95%CI: 0.68–0.86). A similar effect was observed among overweight (0.76; 0.66–0.87) or obese patients (0.53; 0.45–0.63). In contrast, alcohol drinkers experienced a seemingly beneficial effect (1.47; 1.16–1.87). These associations were also observed with other measures of treatment response and were robust to further adjustment for clinical characteristics. Conclusion Smoking and high BMI decrease the odds of bDMARD treatment success in axSpA. Rheumatologists should consider referral to smoking cessation and/or weight management interventions at the time of commencing therapy, to enhance treatment response. The relationship between alcohol and treatment response is unlikely to be causal and warrants further investigation.